Digital-Based Disaster Vulnerability and Mitigation Model: A Study on the Mount Semeru Disaster Area - Sulistyorini Anita; Utomo Muhammad Andry Prio; Izzalqurny Tomy Rizky; Vatrisa Azza Rizqia; Septiani Selsa Tri; Azizi Faaiq Sean Hafidhz; Ferdiansyah Rifaldy Adinandra; Dwirahmadi Febi (BIO Web of Conferences)
Indonesia is located in the Pacific Ring of Fire, rendering it frequently affected by natural disasters, including volcanic eruptions. The country has 127 active volcanoes, with Mount Semeru ranking fourth for the most eruptions in 2022 (36 eruptions). Volcanic eruptions significantly impact nearby communities due to low awareness and preparedness, compounded by the challenges in predicting such disasters. This study aims to develop a disaster mitigation model through a website based on findings in the field. Conducted from July to November 2023 in the Mount Semeru region, the research employed a quantitative approach with a research and development design. The data collection instruments were observation sheets and interview guidelines to analyze needs and develop an information system using the prototyping method. Findings reveal that Mount Semeru's eruptions caused casualties, infrastructure damage, commodity losses, and displacement. Based on the needs analysis, a web-based disaster mitigation model was designed. The website prototype aligns with the conditions of the affected area to significantly reduce the disaster's impact on the community.